Efficacy and epigenetic interactions of novel DNA hypomethylating agent guadecitabine (SGI-110) in preclinical models of hepatocellular carcinoma. Issue 10 (2nd October 2016) - Jueliger, Simone; Lyons, John; Cannito, Sara; Pata, Illar; Pata, Pille; Shkolnaya, Marianna; Lo Re, Oriana; Peyrou, Marion; Villarroya, Francesc; Pazienza, Valerio; Rappa, Francesca; Cappello, Francesco; et al.
ABSTRACT: Hepatocellular carcinoma (HCC) is a deadly malignancy characterized at the epigenetic level by global DNA hypomethylation and focal hypermethylation on the promoter of tumor suppressor genes. In most cases it develops on a background of liver steatohepatitis, fibrosis, and cirrhosis. Guadecitabine (SGI-110) is a second-generation hypomethylating agent, which inhibits DNA methyltransferases. Guadecitabine is formulated as a dinucleotide of decitabine and deoxyguanosine that is resistant to cytidine deaminase (CDA) degradation and results in prolonged in vivo exposure to decitabine following small volume subcutaneous administration of guadecitabine. Here we found that guadecitabine is an effective demethylating agent and is able to prevent HCC progression in pre-clinical models. In a xenograft HCC HepG2 model, guadecitabine impeded tumor growth and inhibited angiogenesis, while it could not prevent liver fibrosis and inflammation in a mouse model of steatohepatitis. Demethylating efficacy of guadecitabine on LINE-1 elements was found to be the highest 8 d post-infusion in blood samples of mice. Analysis of a panel of human HCC vs. normal tissue revealed a signature of hypermethylated tumor suppressor genes ( CDKN1A, CDKN2A, DLEC1, E2F1, GSTP1, OPCML, E2F1, RASSF1, RUNX3, and SOCS1 ) as detected by methylation-specific PCR. A pronounced demethylating effect of guadecitabine was obtained also in the promoters of a subset of tumor suppressors genes ( CDKN2A, DLEC1, and RUNX3 ) in HepG2 and Huh-7 HCC cells. Finally, we analyzed the role of macroH2A1, a variant of histone H2A, an oncogene upregulated in human cirrhosis/HCC that synergizes with DNA methylation in suppressing tumor suppressor genes, and it prevents the inhibition of cell growth triggered by decitabine in HCC cells. Guadecitabine, in contrast to decitabine, blocked growth in HCC cells overexpressing macroH2A1 histones and with high CDA levels, despite being unable to fully demethylate CDKN2A, RUNX3, and DLEC1 promoters altered by macroH2A1. Collectively, our findings in human and mice models reveal novel epigenetic anti-HCC effects of guadecitabine, which might be effective specifically in advanced states of the disease.